ANTIOXIDANT CAPACITY IN SOME TRADITIONAL UGANDAN DIETS - Stangeland, T. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Several studies indicate that a plant-based diet protects against the development of both infectious and non-communicable diseases (NCD) like cancer, diabetes and cardiovascular diseases. It is assumed that the antioxidant content in food is an important reason for this protection. Dietary plants contain several hundred antioxidants, many of which are believed to act in a synergistic way to protect the body against oxidative stress. Sub-Saharan Africa is under a double burden of disease, with the classical malnutrition-related and infectious diseases coexisting with the NCD caused by western influenced diet and lifestyle. The objective of this work was to analyse antioxidant activity (AA) in fruits and vegetables from Uganda and investigate whether AA in traditional food is sufficiently high to prevent oxidative stress and thus combat diseases. We used the FRAP (ferric reducing ability of plasma) procedure. The results showed a great variation in AA ranging from 72.3 Â± 13.5 (Syzygium cuminii seed) to 0.09 Â± 0.05 (Cucurbita maxima fruit) mmol /100g fresh weight (FW). We estimate serving sizes and determine the total antioxidant capacity (TDAC) per day of three traditional Ugandan diets. The dietary plants with highest AA per serving size are pomegranate (Punica granatum), Canarium schweinfurthii, guava (Psidium guajava), mango (Mangifera indica) and tree tomato (Cyphomandra betacea) with values ranging from 8.91 to 3.00 mmol/serving. Of the traditional diets the central/eastern (C/E) and the western (W) diets had almost the same AA (9.31-9.78 and 9.75 mmol/day), while the northern (N) diet had an AA of 7.50-8.02 mmol/day.